Mechanical analysis of prosthetic bars and dental implants in 3 and 4 implant-supported overdenture protocols using finite element analysis - Luiz Bassi-Junior; Rafael Oliveira de Souza Silva; Victor Hugo Dias dos Santos; Abner da Rocha Lourenço; Paulo Vinicius Trevizoli; Hugo Gaêta-Araujo; Polyane Mazucatto Queiroz; Vilmar Divanir Gottardo (Journal of Oral Biology and Craniofacial Research, 2021)
In some clinical situations, the installation of four or more dental implants may be infeasible. Therefore, the installation of protocol-type prostheses with only three implants may be necessary. The mechanical failures can hinder the success of the rehabilitation treatment. Objective: To evaluate and compare the mechanical stress of the metallic prosthetic bar when installed over protocol-type prostheses of three and four implants, and to evaluate the stress on the dental implants. Methodology: Two three-dimensional human jaw models were created. In one model, four dental implants (P4) were designed and in the other model three dental implants (P3) were designed. In both models, according to the arrangement of the dental implants, prosthetic bars were designed. In a finite element analysis software, compressive forces were applied to the ends of both prosthetic bars, simulating the force application during mastication. Tension and stress dissipation were analyzed on the prosthetic bar and dental implants. Results: Both P4 and P3 protocol-type prostheses supported the force efficiently without breaking the bar or the implants. Force dissipation along the bar was more homogeneous in the P3 prosthetic bar than in P4. In addition, P3 implants received a higher concentration of stress in relation to P4 implants. Conclusions: Prosthetic bars and dental implants withstand the stress of load application in both four and three implant protocol-type prostheses. Three-implants protocol showed more satisfactory force dissipation than the four-implant protocol.